An Overview of the Determinants That Escalates Cottage Industry - Pathmananathan, P. Ravindran; Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2021)
In Malaysia, Cottage Industry is a major source of revenue for the villagers. It's mostly small-scale operations that rely on local resources and conventional skills, with low upfront costs and quick returns. However, due to a lack of new technologies, infrastructure, and knowledge transfer, the industry might not be thriving right now. The aim of this research is to evaluate the current roles, challenges, and gaps in Perak's CI. This study was carried out via face-to-face interview on 10 stakeholders from different agencies. This study shows a number of factors affect a community's socioeconomic development and CI business. Internal and external factors, such as interest and self-motivation, as well as the positions of various organisations, as well as family and community support, all contribute to this.